a) \( \lim _{x \rightarrow-\infty} \frac{3 x}{\sqrt{4 x^{2}-2 x+2}} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To find the limit, we can start by simplifying the expression. As \( x \) approaches \(-\infty\), the leading term in the square root will dominate. The expression can be rewritten as: \[ \lim_{x \rightarrow -\infty} \frac{3x}{\sqrt{4x^2 - 2x + 2}} = \lim_{x \rightarrow -\infty} \frac{3x}{\sqrt{4x^2(1 - \frac{2}{4x} + \frac{2}{4x^2})}} = \lim_{x \rightarrow -\infty} \frac{3x}{\sqrt{4x^2} \sqrt{1 - \frac{2}{4x} + \frac{2}{4x^2}}} \] Now, calculate \( \sqrt{4x^2} \): \[ \sqrt{4x^2} = 2|x| = 2(-x) = -2x \quad \text{(since \( x \) is negative)} \] Substituting this back into the limit, we have: \[ \lim_{x \rightarrow -\infty} \frac{3x}{-2x \sqrt{1 - \frac{2}{4x} + \frac{2}{4x^2}}} \] This simplifies to: \[ \lim_{x \rightarrow -\infty} \frac{3}{-2 \sqrt{1 - \frac{2}{4x} + \frac{2}{4x^2}}} \] As \( x \) approaches \(-\infty\), \( -\frac{2}{4x} \) and \( \frac{2}{4x^2} \) trend towards 0. Thus, we have: \[ \sqrt{1 - 0 + 0} = 1 \] Finally, the limit becomes: \[ \frac{3}{-2} = -\frac{3}{2} \] Thus, the limit is: \[ \lim_{x \rightarrow -\infty} \frac{3x}{\sqrt{4x^2 - 2x + 2}} = -\frac{3}{2} \]